Leitura de gêneros textuais em inglês no formato digital na EJA - Santos, Ana Agda de Oliveira (2017)
This study is focused on the analysis of the reading and comprehension process carried out by students from the Youth and Adult Education integrated into the professional technical education in the Federal Institute of Education, Science and Technology of Goiás, in the city of Anápolis, in English classes mediated by Information and Communication Technologies (ICTs). It aims to 1) understand the process of negotiating the meaning of the text – that is, understanding the author’s ideas through the reader’s interaction with the text – shared by students in English reading classes; 2) verify the use of reading strategies, including the electronic translator, in the comprehension of text genres in digital format with the aid of ICTs; 3) discuss the importance of reading text genres in digital format in order to make the youth and adult education students more critical readers, using the technological tools and 4) identify issues related to computer and the Internet use during this process. This research is grounded on studies developed by Bakhtin (2006, 2011, 2013), Lankshear and Knobel (2006), Leffa (1996, 1999, 2006), Marcuschi (2005, 2007, 2008, 2011), Nutall (1996), Oliveira (2013) and some other scholars who approach the subject in question. The methodology used was based on a qualitative case study and in order to generate the data, the reading and writing activities the participants did, questionnaires, interviews and field notes were used. The results showed that the students were able to understand the main ideas of the texts, getting some specific information successfully. However, they used contextual inference strategies and classroom vocabulary minimally and did not make a more critical assessment of the material read. In contrast, they overused the electronic translator to answer the text comprehension activities. The data also showed that some students presented an elementary level of computer literacy and others an intermediate level, whereas, some had a satisfactory level of multimedia literacy and others an unsatisfactory level.